Analisis Resetting Relay Dan Load Presentase Terhadap Pola Pelaksanaan Dan Pemeliharaan Pada Gardu Induk 150 Kv Saketi Banten - Rohmanu Dwi Kuncoro; Ahmad Hermawan; Rhezal Agung Ananto (Elposys: Jurnal Sistem Kelistrikan, 2021)
The Saketi substation has three 150/70 kV power transformers with a capacity of 3x60 MVA with a frequency of 50 Hzwhere all three transformers have the capacity, transformer 1 60 MVA (PAUWELS TRAFO) has 3 feeders with an average load of 300 A, 10 MW, transformer 2 60 MVA (UNINDO) has 3 feeders with an average load of 200 A, 6.9 MW and transformer 3 60 MVA (UNINDO) has 4 feeders with an average load of 300 A, 10 MW. This calculation and simulation analysis is carried out aiming to find out the relay settings on each transformer under normal conditions and in a maintenance state on one of the transformers for a long period of time. From the results of the analysis and calculation, it was found that the OCR relay setting under normal conditions of the incoming 150 kV transformer transformers 1, 2, and 3 has a current setting value of 0.92 A and a time setting of 0.36 seconds. On the outgoing side the 20 kV transformers 1, 2, and 3 have a setting of 1,039 A and a time setting of 0.166 seconds.